2013
DOI: 10.1111/jpn.12083
|View full text |Cite
|
Sign up to set email alerts
|

Content of plasmatic glycerol and activity of hepatic glycerol kinase in broiler chickens fed diets containing different sources and concentrations of glycerine

Abstract: The objective of this study was to evaluate the effect of three sources of glycerine (crude glycerine from soya bean oil - CGSO, mixed crude glycerine from frying oil and lard--MCG, and a semipurified glycerine from soya bean oil--SPGSO) in four concentrations in the diet (17.5, 35.0, 52.5 and 70.0 g of each type of glycerine per kg of feed) on the levels of plasmatic glycerol and the activity of the hepatic enzyme glycerol kinase in broilers of 22-35 days old (experiment I) and 33-42 days old (experiment II).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The increase in hepatic glycerol kinase activity observed in this study suggests that inoculated glycerol was used by the birds (Bernardino et al, 2014). However, sparing effects of amino acids provided by glycerol and benefits related to the weight at hatching and breast yield were not observed.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The increase in hepatic glycerol kinase activity observed in this study suggests that inoculated glycerol was used by the birds (Bernardino et al, 2014). However, sparing effects of amino acids provided by glycerol and benefits related to the weight at hatching and breast yield were not observed.…”
Section: Discussionmentioning
confidence: 55%
“…The activity of liver glycerol kinase was assessed using an adaptation of the methodology presented by Bernardino et al. (). For this, 0.5 g of frozen liver tissue was macerated in a Turrax homogenizer (Ultra‐Turrax T‐25 Basic; IKA‐Werke, Staufen, Germany) with 1.0 ml of 0.05 m Tris–HCl buffer (pH 8.0), and then, the sample was centrifuged (15 000 g for 20 min at 5 °C) and the supernatant collected.…”
Section: Methodsmentioning
confidence: 99%
“…McLea et al (2011) showed that 6.7% glycerin increases dietary nutrient utilization; however, feed conversion ratio increases in broiler chickens above this level. While Bernardino et al (2014) did not observe any saturation of the liver enzyme glycerol kinase with the dietary inclusion of up to 7.0% glycerin, this enzyme is probably saturated above this level because the inclusion of 10% glycerin in broiler diets decreases body and breast weight and increases feed conversion ratio (Cerrate et al 2006). Despite the evidence showing that glycerin levels higher than 5% impair broiler performance, the results from the present experiment and several other studies indicate that glycerin levels higher than 5% are not very detrimental for egg production.…”
Section: Mixed Crude Glycerin In Laying Hen Diets: Live Performance Amentioning
confidence: 99%
“…In the diet, glycerol is generated from triacylglycerides in dietary fat. Crude glycerol or glycerol resulting from digestion of triacylglycerides is passively and actively absorbed in the intestine (Kato et al, 2004;Ohta et al, 2006) and transported to the liver by the bloodstream (Bernardino et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Em frangos de corte, Bernardino et al (2014) encontraram respostas semelhantes, com aumentos no teor de glicerol plasmático com o fornecimento de rações contendo de 0 a 7% de glicerina. Estes resultados demonstram a absorção intestinal do glicerol presente na glicerina e seu transporte até o fígado de monogástricos (TAO et al, 1983).…”
Section: A Origem Do Glicerol E Do Glicerol 3-fosfatounclassified